2017
DOI: 10.18203/2320-1770.ijrcog20174399
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between the efficacy of local intra-myometrial injection of vasopressin and octreotide acetate, in reducing blood loss during myomectomy

Abstract: Background: Symptomatic Uterine leiomyomata may lead to many symptoms including abnormal uterine bleeding, mass pressure effects and infertility. Myomectomy is an option for conservative management, however, it is associated with some disadvantages, mainly increased intra-operative blood loss. Intra-myometrial vasopressin injection during myomectomy is an effective method to decrease the intraoperative bleeding due to its vasoconstrictor effect. Octreotide Acetate (OA) is another vasoconstrictor agent that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[ 15 ] reported that vasopressin (20 units, 1 unit/ml) decreased the blood loss during myomectomy in 26 patients without significant cardiovascular complications and the findings were shown by other studies. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] reported that vasopressin (20 units, 1 unit/ml) decreased the blood loss during myomectomy in 26 patients without significant cardiovascular complications and the findings were shown by other studies. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%